The Crash - McFadden, Freida ([Place of publication not identified] : Thorndike Pr, 2025)
"Tegan is eight months pregnant and her world is crashing down around her. The father of her baby wants nothing to do with her and has promised to make her life hell. She's lost her job at the convenience store, and she has no idea what she's going to do to take care of little one. In a last ditch effort to find help and get away from the threats of her ex, Tegan heads out in a storm to drive to her brother's. But she never arrives. Tegan wakes in a ditch, having skidded off the road. Stranded and terrified, she's taken in by a couple living in a remote farmhouse. But they may have ulterior motives and Tegan soon realizes she's stuck in the middle of nowhere at the mercy of strangers. The nightmare she's running from is nothing compared to where she's headd"--.
ON ORDER RECORD
Keywords: Pregnant women; Unemployment; Strangers; Winter storms; Traffic accidents; Psychological; Suspense fiction